PENGARUH TERPAAN MEDIA DI INSTAGRAM TERHADAP BRAND IMAGE PADA FOLLOWERS AKUN INSTAGRAM @MENANTEA.TOKO - Marisa Mutie Pratiwi (2022)
Nowadays, Instagram is not only a social media for sharing personal photos and videos to other users. However, it is also used to develop the business and brand reach across a range of countries. Instagram is the third most used social media in Indonesia. Based on the result of previous research, Instagram is known as a media which has an influence to build and increase a company's brand image. This study aims to discover how significant media exposure particularly Instagram content advertising or content marketing impacts Menantea's brand image. This research used advertising exposure theory. This research is tested quantitative by using survey method. The population used in this research are followers account Instagram @menantea.toko with the sample of 100 respondents. Sampling in this research uses non-probability sampling with purposive sampling technique. As a result of the analysis, media exposure on Instagram have an impact (37,8%) on brand image of official account Instagram @menantea.toko. Furthermore, the most impactful dimension on this research belongs to attention (media exposure) and strength (brand image).